2009
DOI: 10.1258/td.2009.070497
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia following caesarean deliveries in a rural health district of South Africa

Abstract: The under-treatment of postoperative pain is prevalent worldwide. This cross-sectional study examined general practitioners' (GPs) knowledge and practices regarding postoperative analgesia in Caesarean deliveries. Postoperative analgesia was said to ensure that patients were pain-free (38.7%), achieved early mobilization (19.4%) and enabled early breast feeding (16%). Pethidine was the opioid of choice; normally prescribed eight hourly (69%) and was combined with non-steroidal anti-inflammatory drugs (NSAID) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Still there are many developing countries which are using pethidine like, one study done in rural health district of South Africa [27] has shown pethidine as the most common opioid prescribed (69% of the patients) after CS and intramuscular route was the only route of administration. Our study in spite of this limitation can be helpful to many readers from the developing countries that are still faced with the limited availability of the opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Still there are many developing countries which are using pethidine like, one study done in rural health district of South Africa [27] has shown pethidine as the most common opioid prescribed (69% of the patients) after CS and intramuscular route was the only route of administration. Our study in spite of this limitation can be helpful to many readers from the developing countries that are still faced with the limited availability of the opioids.…”
Section: Discussionmentioning
confidence: 99%
“…The pain was severe in 79.6% of cases 2. In South Africa, it was reported that only 38.7% of patients were pain free 3. Reducing the pain after CS is very important as it has been coupled with more positive emotional status and greater patient satisfaction with postoperative experience 4.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological methods on the other hand include use of medications such as opioids, non-steroidal anti-inflammatory drugs (NSAIDs), epidural or patient controlled analgesia (PCA), and use of local anaesthetics for infiltration into peritoneal cavity and wound infiltration. Pethidine is usually prescribed alone by 51.6% of practitioners 3. Doctors derived their analgesic regimes from current hospital protocols (48.6%), journals (19.45%) or experience (9.7%) 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] One study done in rural health district of South Africa has shown pethidine (69%) as the most common opioid prescribed aft er CS and intramuscular route was the only route of administration. [18] Th ere are also concerns in regard to the potential for systemically administered lipophilic opioids such as pethidine to transfer to breast milk and produce transient adverse neurobehavioral eff ects in the neonate. [19] Although IV-PCA using opioid improves patient satisfaction, better pain scores and less need for rescue analgesia when compared with continuous infusion of opioid, [20] it is also associated with opioid-related side-eff ects and incomplete analgesia.…”
mentioning
confidence: 99%